Age-related diseases, therapies and gut microbiome: A new frontier for healthy aging. (September 2022) - Barone, Monica; D'Amico, Federica; Rampelli, Simone; Brigidi, Patrizia; Turroni, Silvia
Abstract: The gut microbiome is undoubtedly a key modulator of human health, which can promote or impair homeostasis throughout life. This is even more relevant in old age, when there is a gradual loss of function in multiple organ systems, related to growth, metabolism, and immunity. Several studies have described changes in the gut microbiome across age groups up to the extreme limits of lifespan, including maladaptations that occur in the context of age-related conditions, such as frailty, neurodegenerative diseases, and cardiometabolic diseases. The gut microbiome can also interact bi-directionally with anti-age-related disease therapies, being affected and in turn influencing their efficacy. In this framework, the development of integrated microbiome-based intervention strategies, aimed at favoring a eubiotic configuration and trajectory, could therefore represent an innovative approach for the promotion of healthy aging and the achievement of longevity. Highlights: The gut microbiome is a lifelong companion vital to our health. Microbiome imbalances are frequently observed in aging and age-related disorders. Anti-age-related disease therapies interact bidirectionally with the gut microbiome. Microbiome modulation is a new target of precision medicine for healthy aging.